Description of near-tip fracture processes in strain hardening cementitious composites using image-based analysis and the compact tension test - Pereira, E. N. B. (2013)
Strain Hardening Cementitious Composites (SHCC) can be distinguished from other types of fiber reinforced cement-based matrix composites by the typical pseudo-strain hardening behavior they develop in tension. The design of Strain Hardening Cementitious Composites (SHCC) towards the development of multiple cracking in tension is based on the micro-mechanisms involved in the cracking process, including the fiber-matrix interaction properties as well as the fiber and the matrix mechanical properties. The cracking mechanisms at the micro-scale assume a key role in the composite behavior of SHCC. Their complexity introduces, however, significant uncertainty in the entire process. The investigation of the cracking processes of SHCC materials at an intermediate level between the micro-scale and the structural length scale is therefore important to further characterize the influence of the fracture processes on the composite tensile behavior. In previous studies the mechanical behavior of SHCC materials, as well as of other strain softening fiber reinforced cementitious composites, was characterized under eccentric tensile loading using the Compact Tension Test (CTT). The present research further extends this investigation, with particular emphasis on cementitious composites reinforced with multiple types of fibers. The experimental tensile load-displacement results are discussed and compared to the numerically derived responses. To numerically predict the tensile load-displacement responses obtained with the CTTs, the cohesive crack model and the tensile stress-crack opening relationships obtained with the Single Crack Tension Test (SCTT) are utilized. Furthermore, the crack initiation and propagation at the early stages of the loading sequence are analyzed. The size of the specimens and the resolution of the digital images acquired allow the detection of relatively small displacements and crack openings. The results are discussed, with special emphasis on the topology of the cracks obtained near the crack tip and on the description of the fracture process zone.